Ethical Leadership, Leader-Member Exchange and Feedback Seeking: A Double-Moderated Mediation Model of Emotional Intelligence and Work-Unit Structure - Qian, Jing; Wang, Bin; Han, Zhuo; Song, Baihe (Frontiers in Psychology, 2017)
This research elucidates the role of ethical leadership in employee feedback seeking by examining how and when ethical leadership may exert a positive influence on feedback seeking. Using matched reports from 64 supervisors and 265 of their immediate employees from a hotel group located in a major city in China, we proposed and tested a moderated mediation model that examines leader-member exchange (LMX) as the mediator and emotional intelligence as well as work-unit structure as double moderators in the relationships between ethical leadership and followers’ feedback-seeking behavior from supervisors and coworkers. Our findings indicated that (1) LMX mediated the positive relationship between ethical leadership and feedback seeking from both ethical leaders and coworkers, and (2) emotional intelligence and work-unit characteristic served as joint moderators on the mediated positive relationship in such a way that the relationship was stronger when the emotional intelligence and work-unit characteristic were both high.